Tribological performance of electrically conductive and self-lubricating polypropylene–ionic-liquid composites. Issue 12 (10th March 2023) - Gatti, Samuel Franz; Gatti, Felix; Amann, Tobias; Kailer, Andreas; Moser, Kevin; Weiss, Patrick; Seidel, Claudia; Rühe, Jürgen
Abstract : Improved friction and electrical conductivity through self-lubricating polypropylene composites with embedded ionic liquids and carbon-based fillers. Abstract : In this work, self-lubricating and electrically conductive polymers on a polypropylene (PP) matrix were prepared and investigated. These properties were obtained by additivating PP with carbon black (CB) and multi-walled carbon nanotubes (MWCNTs), in combination with a surface active ionic liquid (IL, trihexyltetradecylphosphonium docusate [P66614 ][DOC]). These polymeric composites are expected to achieve coefficients of friction (COFs) comparable to lubricated systems. Combined with electrical conductivity, these materials could be applied in electrically loaded tribosystems. The COF was reduced by up to 25% compared to that of plain PP, and high electrical conductivity and self-lubrication were achieved. Fundamental differences between the carbon-based fillers in their interaction with IL were investigated with high-resolution surface analysis (TEM, AFM) and Raman and ATR-FTIR spectroscopy. By varying the tribological test parameters, the application limits of self-lubrication were identified. It was demonstrated that the contact pressure has a strong influence on the COF. Therefore, this work points to potential applications in ( e.g. 3D-printed) bearings and electrically loaded bearings where electrical conductivity and relatively low COFs are required.